2016
DOI: 10.1515/aopf-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of silver eel (Anguilla anguilla) migrating downstream through a small hydroelectric plant on the Drawa River in northern Poland

Abstract: Abstract. The European eel, Anguilla anguilla L., is an endangered species. Barriers to its downstream spawning migration are one of the greatest threats this species faces. There are hundreds of hydroelectric plants (HEP) on rivers in Poland (> 600), and thousands throughout Europe. Eel that pass through HEP turbines as they migrate downstream suffer high mortality, but this depends mainly on local and technical conditions. Silver eel mortality was estimated and the possibility of the fish bypassing the turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The reversal rate in the Warnow River after the first release was 21%, and 11% after recapture and re‐release. Other studies found reversal rates after first release of 7%‐12% (Dêbowski, Bernas, Skóra & Morzuch, ; Piper et al, ; Piper, Svendsen, Wright & Kemp, ). With regard to Japanese eels for which migratory restlessness was shown to be responsible for their steady descent (Sudo & Tsukamoto, ), more than 70% of the experimental fish displayed “Wanderlust” as well.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The reversal rate in the Warnow River after the first release was 21%, and 11% after recapture and re‐release. Other studies found reversal rates after first release of 7%‐12% (Dêbowski, Bernas, Skóra & Morzuch, ; Piper et al, ; Piper, Svendsen, Wright & Kemp, ). With regard to Japanese eels for which migratory restlessness was shown to be responsible for their steady descent (Sudo & Tsukamoto, ), more than 70% of the experimental fish displayed “Wanderlust” as well.…”
Section: Discussionmentioning
confidence: 89%
“…Stein et al (2016) observed that the animals had to be kept for more than 20 days to terminate the migration of all the eels tested and that the rate of continuation of migration was highest after caging for up to 10 days. The reversal rate in the Warnow River after the first release was 21%, and 11% rates after first release of 7%-12% (Dêbowski, Bernas, Skóra & Morzuch, 2016;Piper et al, 2015;Piper, Svendsen, Wright & Kemp, 2017). With regard to Japanese eels for which migratory restlessness was shown to be responsible for their steady descent (Sudo & Tsukamoto, 2015), more than 70% of the experimental fish displayed "Wanderlust" as well.…”
Section: Influence Of Experimental Designmentioning
confidence: 93%
“…American Eels incurred no mortality or persistent major injuries as a result of passage through the 55‐cm RHT operating at the maximum design head of 10 m. This result is a marked improvement over typical eel mortality and injury rates through conventional Francis and Kaplan turbines, even those with much larger diameters (1.4–6.5 m), for which mortality rates have ranged from 4.9% to 60.0% and can even reach 100% for small crossflow units (Calles et al 2010; Debowski et al 2016; Dainys et al 2017; Heisey et al 2019).…”
Section: Discussionmentioning
confidence: 92%
“…In a Swedish river, Calles et al (2010) found mortality rates of 40% and 60% induced by two plants. At a Polish site, Dębowski et al (2016) estimated a mortality rate of 55%. Mortality due to silver eel fisheries also varies from 22-26% in the Meuse River (Netherlands) (Winter et al, 2006) to 82% mortality in the Gudenaa River and Randers Fjord (Denmark) (Aarestrup et al, 2008) and can reach even higher levels in some Mediterranean lagoons (Amilhat et al, 2008).…”
Section: Using a Theoretical Model To Explore The Possible Consequencmentioning
confidence: 99%